Rituximab pediatric drug development: Pharmacokinetic and pharmacodynamic modeling to inform regulatory approval for rituximab treatment in patients with granulomatosis with polyangiitis or microscopic polyangiitis. Issue 9 (28th June 2022) - Jamois, Candice; Gibiansky, Leonid; Chavanne, Clarisse; Cheu, Melissa; Lehane, Patricia B.; Pordeli, Pooneh; Melega, Simone; Gaudreault, Jacques
Abstract: Anti‐neutrophil cytoplasmic antibody‐associated vasculitides granulomatosis with polyangiitis (GPA) and microscopic polyangiitis (MPA) are rare, potentially organ‐ and life‐threatening autoimmune conditions affecting adult and pediatric patients. An open‐label phase II study was conducted to determine safe and effective dosing regimens of rituximab in pediatric patients with GPA/MPA. To determine the selection of an appropriate dose regimen in children for induction and maintenance, a population pharmacokinetic approach was used (nonlinear mixed‐effect modeling), combining pediatric data with data from adults with GPA/MPA. The time course of B‐cell depletion was assessed in both populations. The exposure‐effect relationship was assessed by logistic regression. Twenty‐five pediatric patients (80% female patients; age range, 6–17 years) were enrolled in the trial and received the induction regimen of intravenous rituximab 375 mg/m 2 weekly for 4 weeks, which resulted in a similar exposure to that of adults. Based on pharmacokinetic modeling, a maintenance dosing regimen of 250 mg/m 2 administered twice over 14 days followed by 250 mg/m 2 every 6 months is expected to result in similar rituximab exposure as that of adults receiving the approved maintenance dose of 500 mg administered twice over 14 days followed by 500 mg every 6 months. The time course of B‐cell depletion was similar between the pediatric and adult populations, supporting the similarities in response in both populations and allowing extrapolation to patients less than 6 years old. Using a partial extrapolation approach helped identify safe and effective dosing regimens of rituximab in pediatric patients with GPA/MPA and lead to regulatory approval.